Pandemic in the Instagram Era. The Visual Analysis of Italian Mayors’ Communication - Piccioni, Tiziana; Riva, Claudio; Micalizzi, Alessandra (Italian Sociological Review, 2023)
Over the last decade, political communication has been affected by a process of disintermediation thanks to the appropriation of social media not only by the networked citizens, but also by politicians, who are increasingly interested in exploring new forms of engagement and participation in the Res Publica (see among others Parisi and Rega, 2010). The opportunities hidden within these new forms of direct communication appeared more clearly during the pandemic crisis when citizens primarily were looking for correct information, practical instructions, and a kind of control of collective anxiety and fear (Jain et al., 2021). The paper aims at presenting the main results of a wider research project conducted by the University of Padua, focused on the role of visual communication in social media platforms of Italian mayors. The study was based on the visual analysis of 54 mayors’ profiles on Instagram between the 21st of April and the 21st of June. Moreover, we carried out 25 in-depth interviews with a subsample of local administrators. Among other goals, we identified the use (pragmatic vs. ideological one) of communicative threads about the pandemic.